Low-temperature biodegradation of freshwater dissolved organic matter during winter-to-spring transition - Bouvet, Corentin; Beauregard, Pascale B.; Guéguen, Céline (Frontiers in Environmental Science, 2025)
The composition of dissolved organic matter (DOM) directly affects the biological degradation processes and its persistence in aquatic systems. Spring floods export large amounts of DOM from land into aquatic systems, yet its lability remains largely unknown. This study uniquely investigates the biodegradation of DOM during the critical winter-to-spring transition in seasonally ice-covered marsh and lake environments. We employed a four-bacteria strain inoculum (Arthrobacter phenanthrenivorans, Bacillus licheniformis, Exiguobacterium sibiricum, and Paracoccus denitrificans) to degrade DOM collected during this period. Using advanced optical and molecular characteristics techniques, we demonstrated significant DOM bioalteration at low temperatures (4°C), which are naturally associated with early spring in cold temperate lakes and wetlands. Despite limited degradation of colored and fluorescent DOM (CDOM and FDOM, respectively), 84% of the mass-to-charge (m/z) peaks detected using positive ion mass spectrometry were lost in winter DOM after 28-day incubation. Biodegradation ranged from 74% to 77% during the spring freshet, with the lowest microbial alteration observed in DOM collected downstream of a marsh at the end of the spring melt season, likely due to increased primary production. These findings highlight the critical role of microbial processes in DOM transformation during periods of rapid hydrological change, providing insights into carbon cycling and ecosystem dynamics in cold aquatic environments.